Productive and reproductive losses associated with abortion in specialized dairy cattle from Costa Rica - Emilia Vindas-van der Wielen; Juan José Romero-Zúñiga; Gustavo Monti (Journal of Dairy Science)
ABSTRACT: Abortions can negatively affect a dairy farm's milk yield, reproductive efficiency, and profitability. Despite the recognized economic losses associated with abortions, the reproductive and productive detriments caused by abortion have not been estimated in dairy cattle in tropical productive conditions such as those in Costa Rica. Therefore, this study aimed to evaluate the potential productive and reproductive losses caused by abortions in dairy cattle from Costa Rica. The reproductive and productive losses caused by abortion were estimated using a dataset with 953,181 complete lactations from 322,873 cows belonging to 1,133 Costa Rican specialized dairy herds. Abortions were classified as early fetal mortality (EFM) and late fetal mortality (LFM). The number of services per conception (NSPC) and calving to effective conception interval (CECI) indicated the reproductive losses. The productive losses were indicated by the DIM per lactation and per cow, productive lifetime, 305-d milk yield per lactation (305-d MY), total milk yield per lactation (TMYPL), and total lifetime milk yield per cow (LTMY). Generalized linear mixed models were adjusted by cow breed, parity, and ecozone, using farm and cow as random effects. Cows that experienced an EFM during the lactation had NSPC increase by 1.61, CECI by 8 d, DIM per lactation by 11 d, 305-d kg by 283 kg, and TMYPL by 297 kg. Cows that experienced a LFM during the lactation had an increase of 0.22 NSPC and a reduction of 33 DIM per lactation, 201 d of productive lifetime, 1,006 kg of 305-d MY, and 1,518 kg of TMYPL. Furthermore, as the parity with abortions increased from 0 to 3 or more, the DIM per cow increased. Still, we found no significant difference in the LTMY when the number of lactations with abortions increased. These results illustrate the impact of abortions on the reproductive and productive performance of cows and, consequently, on the profitability of dairy herds from a tropical country like Costa Rica.